Systematic Screening for Behavior in K–12 Settings as Regular School Practice: Practical Considerations and Recommendations. Issue 4 (2nd October 2017) - Oakes, Wendy Peia; Lane, Kathleen Lynne; Cantwell, Emily D.; Royer, David J.
ABSTRACT: There is a priority for schools to address students' social and emotional needs as is done for academic learning. Tiered models of prevention provide a framework for teaching social skills and behavioral expectations, as well as academics, with positive, proactive, evidence-based practices. Central to responding to students' needs is accurate measurement of their performance. Systematic screening for behavior addresses this need. Specific screening tools are presented with brief evidence for their use. Then practical considerations and recommendations are offered for school leadership teams as they plan for using systematic behavior screening as a regular school practice. The study was framed within tiered models of prevention; however, screening practices may be used outside of tiered models provided structures are in place for responding to student needs when detected. Content is offered to guide school leadership teams as they undertake systematic behavior screening efforts.